High frequency model for power electronics capacitors. - Siami, S. (IEEE Transactions on power electronics)
The study of metallized capacitor behavior at high frequencies points out the presence of series and parallel resonances that could lead to oscillations, perturbations and additional losses in power electronics apparatus. Starting from an already established analytical model of this resonance, we propose a method to elaborate equivalent circuits suiting circuit simulators. These models should help further investigations on high frequency properties of decoupling and snubber capacitors in commutation cells